VIRGILIO (ENEIDA) Y OVIDIO (METAMORFOSIS): DOS TRANSMISIONES TEXTUALES DISIMÉTRICAS - Escobar, Ángel (Exemplaria Classica, 2017)
Although the respective textual transmissions of Virgil’s Aeneid and Ovid’s Metamorphoses share some similarities, there are also some clearly distinctive features, which allow us to qualify them as ‘asymmetric’ textual traditions. However, this does not imply that a specific methodological approach must be adopted in order to study the textual variation in each tradition, nor to establish each text.